Related factors with Diabetes Mellitus type II events at posyandu lansia of Puskesmas Pisang Baru Subdistrict Bumi Agung District Way Kanan - Anggie Stiexs; Dian Arif Wahyudi; Didi siswanto; Widia Astuti (Universitas Aisyah Pringsewu, 2023)
Elderly experience a lot of decline in both physical and mental function, one of the degenerative diseases that become an important problem in elderly is diabetes mellitus (DM) where the type of DM in the elderly is generally DM type II number of elderly as many as 100,390 people and recorded that suffered diabetes mellitus of 1,614 inhabitants (Right Way Health Office, 2017). This study aims to determine the relationship between obesity, physical activity, age with the incidence of type II Diabetes Mellitus in participants in Posyandu elderly working area of PisangBaruPuskesmas, the type of research using quantitative research with cross sectional approach, the population is all elderly in the work area of Pisangmas Baru Bumi Agung District, Way Kanan District in 2018 amounted to 358 people and sampled as many as 189 elderly by accidental sampling. The analysis used chi-square test (p = 0,05). The result of the research was obtained: IMT variable p-value = 0,001, physical activity variable p-value = 0,001, age p-value = 0,001, so it was concluded that there was a significant correlation between obesity, physical activity and age with type II diabetes mellitus work Puskesmas Pisang Baru Sub District Bumi Agung District Way Kanan in 2018. Suggestion that writer ask is: to improve quality and performance of health officer in implementation of poyandu elderly with posyandu routine every month, weekly elderly gymnastics once and once monthly, socialization of nutrition menu balance for elderly accompanied with nutrition consultation for patient of diabetes mellitus. Abstrak: Lansia mengalami banyak penurunan fungsi baik fisik dan mental, salah satu penyakit degeneratif yang menjadi masalah penting pada lansia adalah diabetes mellitus (DM) dimana jenis DM pada lansia umumnya adalah DM tipe II Total Lansia sebanyak 100.390 jiwa dan dicatat yang menderita diabetes mellitus sebesar 1.614 jiwa ( Dinkes Way Kanan, 2017). Penelitian ini bertujuan untuk mengetahui hubungan antara indeks masa tubuh, aktivitas fisik, usia dengan kejadian Diabetes Millitus tipe II pada peserta di posyandu lansia wilayah kerja Puskesmas Pisang Baru, jenis penelitian menggunakan penelitian kuantitatif dengan pendekatan cross sectional, populasinya adalah seluruh lansia dalam wilayah kerja Puskesmas Pisang Baru Kecamatan Bumi Agung Kabupaten Way Kanan tahun 2018 berTotal 358 orang dan diambil sampel sebanyak 189 lansia dengan cara accidental sampling. Analisis penelitian menggunakan uji chi square (p=0,05). Hasil penelitian diperoleh: variable IMT p-value= 0,001, variable aktifitas fisik p-value = 0,001, variable usia p-value = 0,001, sehingga disimpulkan ada hubungan yang bermakna antara obesitas, aktivitas fisik, dan usia dengan kejadian diabetes mellitus tipe II wilayah kerja Puskesmas Pisang Baru Kecamatan Bumi Agung Kabupaten Way Kanan tahun 2018. Saran yang penulis ajukan adalah: meningkatkan mutu dan kinerja petugas kesehatan dalam pelaksanaan poyandu Lansia dengan posyandu rutin setiap bulan, senam lansia 1 minggu sekali dan pemeriksaan rutin 1 bulan sekali, sosialisasi menu gizi seimbang untuk lansia disertai dengan konsultasi gizi untuk penderita diabetes mellitus.